KARAKTERISTIK MODAL SOSIAL PETANI CABAI KOPAY DI KOTA PAYAKUMBUH - Ernanda, Revi; Burhanuddin, Burhanuddin; Purwiono, Joko (Jurnal AGRISEP, 2019)
This paper is aimedat analyzing the social capital ofkopay chili farmers in Payakumbuh City. The characteristicsof social capitalon the kopay chili farmerswere analyzed descriptively from 53 farmers selected using snowball sampling. Thesefarmershadwith longexperiencesin conductingkopay chili farmingin Payakumbuh.The result of the study showedthat the social capital of kopay chili farmers consisted of excellent trust, social norms and networks. Social capital variable havinga high level of farmers perceptionare social norm, namely,activities that help each other amongfarmers. Social capital gave abeneficial for farmers in supporting their farmingactivities. Therefore, the government shouldpay attention to social capital indesigning theagriculturaleducationstrategies for improvingthe kopay chili farmersperformances.